Turkish Adaptation of Leisure Motivation Scale: A Sample of Turkish Adolescents Participating in Regularly Physical Activity - Mehmet Ceylan; Serdar Solmaz; Buğra Akay; Fatih Yaşartürk; İsmail Aydın (Atatürk University, 2024)
In the study, we aimed to evaluate the Turkish adaptation of the leisure motivation scale (LMS-A) for adolescents participating in recreational physical activities. We collected data from 331 people determined by the convenience sampling method, and conducted its Turkish adaptation with three different test phases after we performed Turkish language co-validation of the scale. Firstly, we determined the univariate and multivariate normality levels of the data. In the second stage we used confirmatory factor analysis (CFA) to assess the contextuality of the scale and in the third stage we utilized two types of construct validity, convergent and discriminant to evaluate the validity of the scale. The results revealed that the original structure of the scale fits well in the correlated factors model and best fit the data collected from the Turkish population. These results suggest that the leisure motivation scale could be a valid and reliable measurement tool for adolescents participating in recreational physical activities in Türkiye.